Le cose non sono quello che sembrano contributi teorico-analitici per una sociologia non ovvia. Sulla traccia di Luciano Gallino - Pacelli, Donatella (Teorie sociologiche e trasformazioni sociali - Open Access, 2017)
"The essays collected in this volume wonder about different aspects of the crisis we are experiencing and discuss the interpretative models best suited to approach them. From the actor's theory to the transition theories; from the degenerations of capitalism and liberalism to the role of Europe; from the social implications of science to the transformations that affect work; from the training to the experiences of the young generations, we have here a path that combines theory and social research, rigorous observations and images of a better world."